Mutual Authentication Protocol Model For Low-Cost RFID Systems Based On Shelled Random Value - al-Dala'ien, Mu'awya Naser Salam (2011)

(untitled)
Designing a reliable secure low-cost protocol for radio-frequency identification (RFID) is difficult, standard cryptographic primitives can become a limitation for low-cost tags due to their costly large requirements in terms of circuit size, power consumption, and memory size. Therefore, ultralightweight cryptography in designing low-cost RFID protocols capable of executing data communication sessions efficiently and effectively are needed to solve database loading, passive attacks, desynchronization and high computational cost problems.